First report on metagenomics and their predictive functional analysis of fermented bamboo shoot food of Tripura, North East India - Das, Rohit; Tamang, Buddhiman; Najar, Ishfaq Nabi; Thakur, Nagendra; Mondal, Krishnendu (Frontiers in Microbiology, 2023)
Moiya pangsung, mileye amileye, moiyakoshak, and midukeye are naturally fermented bamboo shoot foods of Tripura. The present study aimed to reveal the whole microbial community structure of naturally fermented moiya pangsung, mileye amileye, moiya koshak, and midukeye along with the prediction of microbial functional profiles by shotgun metagenomic sequence analysis. The metataxonomic profile of moiya pangsung, mileye amileye, moiya koshak, and midukeye samples showed different domains viz. bacteria (97.70%) followed by the virus (0.76%), unclassified (0.09%), eukaryotes (1.46%) and archaea (0.05%). Overall, 49 phyla, 409 families, 841 genera, and 1799 species were found in all the fermented bamboo shoot samples collected from different places of Tripura. Firmicutes was the most abundant phylum (89.28%) followed by Proteobacteria (5.13%), Bacteroidetes (4.38%), Actinobacteria (1.02%), and Fusobacteria (0.17%). Lactiplantibacillus plantarum was the most abundant species in moiya pangsung, mileye amileye, moiya koshak, and midukeye followed by Lactococcus lactis, Levilactobacillus brevis, Leuconostoc mesenteroides, Weissella paramesenteroides, Leuconostoc kimchii, Pediococcus pentosaceus, Leuconostoc gasicomitatum, and Lacticaseibacillus casei. A few phyla of fungus were found viz. Ascomycota, Basidiomycota, and Glomeromycota, where Ascomycota was present in high abundance. Functional analysis of moiya pangsung, mileye amileye, moiya koshak, and midukeye metagenome revealed the genes for the synthesis and metabolism of a wide range of bioactive compounds including, various essential amino acids, and conjugated amino acids. The abundance profile and predictive analysis of fermented bamboo shoots revealed a huge plethora of essential microorganisms and KEGG analysis revealed genes for amino acid metabolism, pectin degradation, lipid metabolism, and many other essential pathways that can be essential for the improvement of nutritional and sensory qualities of the fermented bamboo shoot products.